Sistem Pendukung Keputusan Penilaian Kinerja Karyawan PT Harjamukti Jaya Mandiri Menggunakan Metode Simple Additive Weighting - Apriyanto Noer Setiawan; Petrus Sokibi (ITEJ (Information Technology Engineering Journals), 2017)
Assessment of the performance is an important process from whole employees activity, assessment of the performance can do for enhancement position, give salary bonus and evaluation from performance result of employees with the properties of the objective assessment. Decision Support System Assessment of the Employees Performance is a system can help division Staff Manager PT. HARJAMUKTI JAYA MANDIRI in determines decision employees with good performance to get a salary bonus. The method used on this system is Simple Additive Weighting which uses predefined criteria in a calculation. Criteria used for measure performance of employees there are 5, there are work discipline, last education, work experience, teamwork and liveliness and the criteria used in this system are a benefit.